Atwood in numbers - Tutek, Nikola (ELOPE (Ljubljana), 2020)
This paper offers analyses of the semantic interrelations between illustrations and written text in short stories from two flash fiction collections by Margaret Atwood: Bones and Murder(1994) and The Tent (2006). The analyses are based on the technical, generic, and thematic features of the illustrations, on the influences traceable in both illustrations and texts, and on the set of defined multimodal interrelations. The results of the analyses are expressed numerically and comparatively.
Keywords: Atwood, Margaret; flash fiction; flash fikcija; illustrations; ilustracije; multimodality; multimodalnost